Changes in frigate tuna populations on the south coast of Sri Lanka: evidence of the shifting baseline syndrome from analysis of fisher observations - Venkatachalam, A.J.; Price, A.R.G.; Chandrasekara, S.; Senaratna Sellamuttu, Sonali; Kaler, J. (Wiley, 2010)
This study examines changes in frigate tuna populations in southern Sri Lanka, based on reports from fishers in three age classes. Significantly higher values for best day's catch and largest specimen ever caught were obtained by older fishers than younger ones. Values were also significantly higher during early years, providing clear evidence of a decrease in the resource over time (1951-2007). Older fishers reported best catches further inshore and in shallower waters which, on becoming depleted, forced younger generations to fish in less exploited areas further offshore. Heavy harvesting is also evident from the significantly greater number of sites reported by older fishers as being depleted, compared with observations of younger fishers. These findings contrast markedly with catch and catch per effort patterns from statistics for frigate tuna and bullet tuna (combined) in southern Sri Lanka (1994-2004). No stock decline is evident, and at least one report in the early 1990s advocated increasing exploitation rates by 40% to maximize yields. Although not a primary research objective, fisher observations on frigate tuna populations were also analysed to help evaluate possible effects of the 2004 tsunami. Most fishers reported post-tsunami decline, but mainly from a larger new generation of fishers, rather than extra boats provided by aid money or (direct or indirect) biophysical impacts from the tsunami. Reliance on fishery statistics, especially for mixed species and over a limited period, can be risky and easily mask true stock status. Evidence of harvesting effects on frigate tuna in southern Sri Lanka is evident using questionnaire data over a longer time scale. This study provides another compelling case of the 'shifting baseline syndrome', whereby fishers of different ages have altered perceptions/experiences of their environment. This may be its first reported occurrence in Sri Lanka. Traditional knowledge from this and similar surveys may provide national fishery management with valuable insights and help improve conservation prospects for frigate tuna and other marine resources.